Pengaruh Penerapan E-SPT, Pengetahuan Dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Hadian Wibowo; Endang Mahpudin (COSTING : Journal of Economic, Business and Accounting, 2021)
This research aims to find out and test the influence of E-SPT Implementation, Knowledge and Socialization on Personal Taxpayer Compliance in TelukJambe Village. The study used quantitative methods using primary data obtained from questionnaires. The population in the study was 620 people. The sample in this study was 86 respondents. The sampling technique used is Purposive Sampling. The results showed that the Implementation of E-SPT had no significant effect on Taxpayer Compliance, Knowledge had a significant effect on Taxpayer Compliance and Socialization had no significant effect on People's Taxpayer Compliance. The influence of E-spt, Knowledge and Socialization together affects Taxpayer Compliance. Keywords: Implementation of E-SPT, Knowledge and Socialization, Taxpayer Compliance